Structural credit ratios - Benedetta Bianchi (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
This paper studies the relation between the credit-to-GDP ratio and macroeconomic trends. We estimate a long run equation on a sample of EU countries; our findings suggest that the macroeconomic factors with which the credit ratio associates most strongly are economic development, the investment share in GDP, and inflation. We then obtain projections for past and future trends. First, we study the evolution of the credit ratio in the past. We find that most of the increase starting in 1985 is associated with economic development and falling inflation, while the decrease of investment may have slowed down this trend. Second, we offer a forward-looking estimate of the structural credit ratio, defined as the long run, or sustainable, component. We offer band estimates based on two alternative assumptions on future economic outcomes, which can be interpreted as a structural and a cyclical view of current macroeconomic dynamics. Estimates of structural credit ratios based on this method are useful to policy makers having to decide on the activation of the countercyclical capital buffer, especially when assessing the sustainability of credit growth.
Keywords: E51; G01; E44; 330; Equilibrium credit; Credit gap; Macro-prudential analysis; Long run modelling